Effects of cervical traction with and without EMG biofeedback in patients with cervical radiculopathy- A randomised controlled trial - Sana Sabir; Maria Khalid; Azam Khan, Kiran; Zainab Noor Qazi; Summaiyah Obaid; Sania Khawar (Journal of the Pakistan Medical Association, 2026)
Objective: To find out the effects of cervical traction with and without electromyography biofeedback on range of motion, pain, level of disability and muscle tension. Method: The randomised controlled trial was conducted at the Fauji Foundation Hospital, Rawalpindi, Pakistan, from July 2021 to July 2022, and comprised patients aged 30-50 years having radicular symptoms persistent for 1-6 months, and underwent cervical traction. The subjects were randomly allocated to Group A with electromyography biofeedback, and Group B without electromyography biofeedback. Both the groups received conventional therapy including hot pack, transcutaneous electrical nerve stimulation, cervical mobilisation and isometrics. The frequency of the treatment was 2 sessions per week over 6 weeks. Data was collected at baseline, after 2, 4 and 6 weeks. Data collection tools included visual analogue scale, neck disability index, inclinometer and electromyography biofeedback. Data was analysed using SPSS 21. Results: Of the 44 patients, 22(50%) were each of the two groups. In Group A, there were 16(72.7 %) females and 6(27.3 %) males with mean age 43.72+6.71 years. Group B had a similar gender distribution while the mean age was 43.95+5.58 years. In both the groups, neck pain and cervical range of motion improved significantly post-intervention (p<0.05), but Group A values were significantly better than Group B (p<0.05). Cervical disability and muscular tension were not significantly different in both intragroup and intergroup comparisons (p>0.05). Conclusion: Cervical traction with added electromyography biofeedback effectively lowered cervical pain intensity and improved cervical range compared to cervical traction alone. Electromyography biofeedback showed no additional benefits in managing disability and muscular tension. RCT registration Number: Clinical Trials. govt with ID: NCT05352464. Key Words: Radiculopathy, Cervical, Electromyography feedback, Cervical pain, Tractions, Visual analogue scale.